Diagnostic petiole nntrieant norms and identification of yidd limiting lnutrrients in papaya (Capz'ea papaya) using diagnosis and recommendation integrated system - ANJANEYULU, K (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted during 2004-05 to study the petiole nutrient norms using diagnosis and recommendation integrated system from 60 papaya (Carica papaya) gardens. A total of 300 samples were collected (sixth petiole from apex) to analyze for macro and micronutrients for establishment of the data bank. The whole population was divided into 2 sub-groups, namely low and high yielding by using diagnosis and recommendation integrated system and thus selected 45 nutrient expressions as diagnostic norms. These expressions had shown higher variance and lower coefficient of variation that are found to have greater diagnostic precision, viz NIP (6.368), N/K (0.571), Mg/N (0.899), NlZn (0.045), Ca/Mn (0.062), CaIZn (0.115), Mg/Zn (0.039) and SIZn (0.010) etc. The nutritional balance index indicates the overall imbalance of the nutrient-based on sum of the indices irrespective of sign. The diagnosis of nutrient imbalance through diagnosis and recommendation integrated system indices indicated that the most common yield-limiting nutrient is zinc, followed by potassium. In addition, 5 nutrient ranges have been derived using mean and standard deviation as low, deficient, optimum, high and excess for each nutrient to serve as a guide for diagnostic purpose. The optimum N ranged from 0.91 to 1.44%, P from 0.12 to 0.28%, K from 2.22 to 3.75%, Ca from 2.65 to 4.19%, Mg from 0.67 to 1.37% and S from 0.18 to 0.37%. Among the micronutrients the optimum Zn ranged from 17 to 40 ppm, Fe from 33 to 92 ppm, Mn from 34 to 60 ppm and Cu from 6 to 12 ppm for papaya.